Causes, risk factors and complications of dental implant failure - S. Alfaer, Ali; F. Aljabr, Renad; A. Alharthi, Wejdan; A. Alhazzani, Hisham; Owaywid, Abdullah N. Bin; H. Alwadai, Adel; M. Alnaiem, Nahaia; E. Almalki, Hussam; A. Alqahtani, Abdulaziz; A. Mobaraky, Abdulrahman; M. Alasmari, Amjad (International Journal Of Community Medicine And Public Health, 2023)
Osseointegration, which refers to the direct attachment of dental implants (DIs) to the neighboring host bone, is a great predictor of the therapeutic efficacy of DIs. The factors that determine whether DIs are successful have been evolving over time. Presently, these factors comprise the lack of mobility at the beginning of the prosthetic stage. DIs have a high chance of success; however, they occasionally fail. The failure of properly implanted DIs has been attributed to inappropriate patient identification; inadequate dental hygiene associated with microbial plaque buildup. The three most significant factors that lead to early implant failure appear to be a paucity of basic stability, surgical injury, and infection. Due to disruption of the basic bone recovery process, initial symptoms of infection may portend a far more serious outcome than if similar issues arise later. It appears that peri-implantitis and occlusal overloading are the main causes of late failure. Among the predisposing variables for implant problems and failure include poor prosthesis fabrication and subpar implant design.